Media Relations Video Learning and Motivation to Learn The Skills of Writing Poetry In Class X high School Private Bodhicitta Medan The Academic Year 2021/2022 - Sukawi (CV. AFDIFAL MAJU BERKAH, 2022)
This study aims to determine the relationship of instructional media fucking with the skills to write poetry, the relationship of motivation to learn the skills of writing poetry, and determine the relationship of media video learning and motivation learning together with writing skills of the poetry of the students of class X Private high school Bodhicitta Medan academic year 2021/2022. This research was conducted in SMA SwastaBodhicitta Terrain of Class X of a population of 78 people, and the number of samples is overall the students of class X amount to 78 students with the use of quantitative methods as well as data obtained using the instrument questionnaire and documentation. Data analysis using the t test (t-test) for the correlation sderhana and the F test (F-test) for the multiple correlation. These findings indicate: 1). The t value to the variable (X1) with (Y) = 0,012 with the t table at a significance level of 5% = 1,984. 2). The t value to the variable (X2) with (Y) = 1,259 with the t table at a significance level of 5% = 1,984. 3). Calculated F value for the variable (X1) and (X2) together with (Y) = 1,09 with the F table at the significance level of 5% = 3,087. The conclusion of this study explain that the absence of a positive relationship and significant correlation between learning media fucking with the skills to write poetry students and the absence of a positive relationship and significant correlation between learning motivation with the skills to write poetry students, as well as the absence of a positive relationship and significant between media video learning and motivation to learn the skills of writing poetry class X Private high school Bodhicitta Medan academic Year 2021/2022